Culture-based teaching practices of teachers in a Philippine-Chinese school: narratives and insights - Bacus, Remedios C.; Alda, Rivika C.; Boholano, Helen B. (International Journal of Evaluation and Research in Education (IJERE), 2025)
Philippine-Chinese schools have been in existence for several decades. This study explores the influence of Chinese culture on Filipino teachers’ pedagogical and content delivery, language and social interaction, and their practices and constructions while teaching in a Chinese school. Through a descriptive–qualitative approach to explore the experiences, 12 non-Chinese teachers were purposively chosen to participate in the study. Guided by the validated interview guide and the qualitative data analysis steps by Braun and Clarke, six themes emerged: bilingual pedagogy, cultural values integration, language immersion, technology in education, thriving through diversity, support and collegiality. The study revealed the enriching interaction between Chinese cultural influences and Filipino teaching practices, suggesting the need for ongoing professional development that enhances cultural competence, innovative pedagogical strategies, and supportive teaching communities.